Lone parents, employment and social policy : cross-national comparisons / edited by Jane Millar and Karen Rowlingson. - Millar, J.; Rowlingson, Karen (Policy Press, 2001)
Policy makers across the world confront issues relating to lone parents and employment, with many governments seeking to increase the participation of lone parents in the labour market. This book offers an analysis of policies and provisions in several countries, identifying policy lessons. Chapters are written by experts on lone parenthood.